ANALISIS PENENTUAN PROGRAM RUANG PADA GELANGGANG OLAHRAGA BULUTANGKIS DI KABUPATEN PASURUAN - Bahza, Al Fitrah Afifah Bahza; Mascruchin, Febby Rahmatullah; Hersanyo, Benny Bintarjo Dwinugroho (Jayabama: Jurnal Peminat Olahraga, 2025)
Pasuruan Regency has significant potential in developing badminton as a leading sport. The popularity of badminton in this area continues to increase along with the high public interest and emerging young athletic talents. However, the lack of adequate sports facilities is the main obstacle in optimizing this potential. Existing facilities do not meet the necessary standards for intensive training or quality competitions. A brief literature review highlights various approaches in sports arena design. Research by [Researcher A] emphasizes the importance of integrating flexible spaces to support various activities, while [Researcher B] shows that natural ventilation and appropriate lighting improve user comfort. Although these solutions are effective in certain contexts, most previous studies have not considered the specific needs of local communities, such as user characteristics,climate, and local culture. This research aims to address these limitations by designing a space program that not only meets national and international standards but also aligns with the unique needs of Pasuruan’s community. Thus, this research offers a new approach that combines universal design principles with a local context. The novelty of this paper lies in its focus on local community needs, which can serve as a model for designing similar facilities in other areas. Additionally, this research is expected to contribute scientifically to the development of efficient and contextual sports facility designs